The Role Of Preventive Medicine In Strengthening Children’s Health - Tursunov, Muhammadaziz; Ganiyev, Nodirbek (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article discusses preventive measures in the field of pediatrics in maintaining and developing children’s health and their importance in medicine. Basically, the issues of preventing common childhood diseases, proper nutrition, immunization, compliance with hygiene rules, and improving the psychological environment are presented in a popular scientific style. Social factors and modern medical approaches affecting children’s health are also analyzed. Theoretical and practical aspects of prevention are studied, and current problems and prospects in pediatrics are highlighted.